Advances in Engineering Design Select Proceedings of FLAME 2018 - Prasad, Anamika; Gupta, Shakti S.; Tyagi, R. K. (Lecture Notes in Mechanical Engineering, 2019)
This book presents select proceedings of the International Conference on Future Learning Aspects of Mechanical Engineering (FLAME 2018). The book covers mechanical design areas such as computational mechanics, finite element modeling, computer aided designing, tribology, fracture mechanics, and vibration. The book brings together different aspects of engineering design, and will be useful for researchers and professionals working in this field.